Comparative Study to Assess the Effects on Blood Pressure of Drinking Green and Black Tea among Hypertensive Patients - P Meena; Meenakshi Jayakumar (Journal of Pharmacy and Bioallied Sciences)
Hypertension is a serious condition that affects both industrialized and developing nations’ public health. It is an important medical condition that can raise the chance of developing heart, brain, kidney, and other problems. Objective: • To evaluate the effect of green tea and black tea on blood pressure (BP). • To compare the levels of BP among black tea- and green tea-consuming hypertensive patients. • To find out the association between effects of green tea- and black tea-consuming hypertensive patients with selected demographic variables. Methodology: A quasiexperimental research design with the purposive sampling technique was adopted to conduct a study among 60 hypertensive patients. Thirty patients consume black tea, and 30 consume green tea. Data were gathered by structured questionnaires using demographic variables and biological parameters. Result: The calculated Student independent ‘t’ test value of t = 3.216 in the post-test shows that there was a statistically significant difference between the post-test levels of systolic BP between the two groups, which was statistically significant at P < 0.01 level. The calculated student independent‘t’ test value of t = 2.986 in the post-test shows that there was a statistically significant difference between the post-test levels of diastolic BP between the two groups, which was statistically significant at P < 0.01 level. Conclusion: Green tea was found to be more effective than black tea in reducing the level of hypertension among the hypertensive clients.